Does Executive Compensation Reinforce the Influence of Political Connection and Investment Opportunity Set on Firm Value? - Kholid, Arif Wahyu Nur; Rahmawati, Evi (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purpose: Executives may be crucial in managing the political connection and investment opportunity set (IOS). Compensations are given to motivate executives to enhance their performance to manage it. Therefore, this study examined the moderation of executive compensation in the influence of political connections and IOS on the firm value.Method: The study used samples of all listed companies in IDX and applied a quantitative approach from 2015 to 2020. Research data were obtained from www.idx.co.id and OSIRIS. This research employed a purposive sampling method, with a firm year of 1,242 observations. Hypothesis testing was carried out utilizing multivariate regression using panel data. This research used the Fixed Effect Model to process the data and employed the different proxies for measuring IOS to examine the robustness model.Findings: This study discovered that IOS positively affected firm value. Furthermore, using different measurements of IOS, this study consistently found that IOS positively affected firm value. Moreover, when IOS was measured by MVBV, the moderating variable of executive compensation provided significant results because there was a wedge of measurement between the MVBV and Tobin’s Q. However, this study could not find that executive compensation had a moderate effect. It indicated that the executive compensation could not reinforce the interaction between IOS and political connections on firm value. In addition, political connections did not influence the firm’s value. On the other hand, the IOS positively affected firm value. Even though IOS was regressed using another proxy, i.e., MVBV and Net PPE, the result was still reliable that IOS positively affected firm value.Novelty: This study was developed from previous research by considering executive compensation as a moderating variable and examined two proxies to measure the IOS and developed one proxy, i.e., net PPE ratio, to measure IOS. Furthermore, this study used the balance panel method, with an observation period of six years.